1984
DOI: 10.1111/j.1365-2478.1984.tb01107.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Determination of the Downgoing P‐waves Radiated by the Vertical Seismic Vibrator*

Abstract: It is well recognized that in order to realize the full potential of the Vibroseis technique, one needs to ensure accurate phase locking and a meaningful cross‐correlation. To achieve these two important objectives we require an accurate estimate of the compressional stress wave radiated by the vibrator into the ground. In this paper a simple method (subject of a patent application) is developed for predicting the compressional stress waves radiated by a vertical vibrator. The main feature of the proposed meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Groundforce is typically approximated using the mass weighted sum of the reaction mass and baseplate accelerations (Castanet and Lavergne 1965; Sallas 1984). In the absence of shear stress at the contact surface, the far‐field particle displacement downhole, due to P‐wave radiation from an acoustically small disc vertically oscillating at the surface, in the theoretical world of elastic isotropic half‐spaces, has the same spectral shape except for time delay as the groundforce (Miller and Pursey 1954; Safar 1984). For small sources, it can be shown that the distribution of the vertical stress applied over the contact area need not be uniform and that the same relationship holds between the resulting groundforce and far‐field particle motion (Baeten and Ziolkowski 1990).…”
Section: Some Basicsmentioning
confidence: 99%
“…Groundforce is typically approximated using the mass weighted sum of the reaction mass and baseplate accelerations (Castanet and Lavergne 1965; Sallas 1984). In the absence of shear stress at the contact surface, the far‐field particle displacement downhole, due to P‐wave radiation from an acoustically small disc vertically oscillating at the surface, in the theoretical world of elastic isotropic half‐spaces, has the same spectral shape except for time delay as the groundforce (Miller and Pursey 1954; Safar 1984). For small sources, it can be shown that the distribution of the vertical stress applied over the contact area need not be uniform and that the same relationship holds between the resulting groundforce and far‐field particle motion (Baeten and Ziolkowski 1990).…”
Section: Some Basicsmentioning
confidence: 99%
“…If the contact is complete ͑infi-nitely stiff͒, no deformation of the springs occurs and z 2 = z 3 . This reduces equations 1 to the linear vibroseis model ͑Lerwill, 1981; Sallas and Weber, 1982;Safar, 1984;Sallas, 1984͒. We will use two rigidity profiles. The first is the model of bimodular contact as considered by Lebedev and Beresnev ͑2004͒.…”
Section: Model Formulation -Bimodular and Smooth Profiles Of Contact mentioning
confidence: 99%
“…Furthermore, the contact region is typically much softer than the other parts of the interacting bodies ͑the baseplate and the consolidated material below͒; as a result, the deformations in this intermediate region are large enough to change the spectrum of radiation considerably. A model of such a contact and its effect on radiation were discussed by Lebedev and Beresnev ͑2004͒. In the equivalent scheme of the vibroseis source ͑Lerwill, 1981; Sallas and Weber, 1982;Sallas, 1984;Safar, 1984͒, this nonlinearity can be accounted for by introducing a contact spring with the rigidity K c = −dF c /dx ͑Lebedev and Beresnev, 2004͒, where x ϵ z 2 − z 3 , F c is the restoring force from the contact deformation, and z 1 , z 2 , and z 3 are the displacements of the reaction mass, baseplate, and the ground beneath the plate, respectively ͑Figure 1͒. The system of equations governing the source then becomes ͑Leb-edev and Beresnev, 2004͒…”
Section: Model Formulation -Bimodular and Smooth Profiles Of Contact mentioning
confidence: 99%
See 1 more Smart Citation
“…The vibrator ground force can be approximated by using a ‘weighted sum’ of accelerations of the reaction mass and the baseplate (Sallas 1984; Safar 1984; Baeten and Ziolkowski 1990). The weighted‐sum method is built on the rigid body assumption of the baseplate.…”
Section: Vibrator Baseplate Flexure and Weighted‐sum Ground Forcementioning
confidence: 99%